Recording of f luorescence from the probes based on polymethine dyes in the tissues in vivo - Voropay, Eugene S.; Samtsov, Michael P.; Lyashenko, Lyudmila S. (Journal of the Belarusian State University. Physics, 2017)
A high level of light scattering and intrinsic luminescence of biological tissues in vivo interfere with correct recording of signals from fluorescent probes in such systems. This work presents the optimized conditions for recording of polymethine dye fluorescence in the tissues in vivo. It has been found that, to lower the effect of intrinsic luminescence of biotissues when fluorescence is recorded in vivo over the spectral range 710 – 900 nm, the wavelength of laser sources used for excitation should be above 676 nm. It has been shown that the use of a СЗС-20 absorption light filter revealing no luminescence over the spectral range under study is optimal to lower in a spectrometer a level of scattered light from the excitation laser (l = 682 nm) by three orders. By scanning an optical fiber over the surface of the tumor node, it has been demonstrated that in the case of necrotic tissues the fluorescence signal of polymethine dye in this region is lower by a factor of 3–5 as compared to other parts of the tumor.
Keywords: polymethine dyes; fluorescence recording; in vivo; photoactivity